Interstitial ectopic pregnancy: a case series - Gnanavel, Gitanjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Interstitial ectopic pregnancy is very rare with incidence of 2-5%. Their presentation is not uniform and hence may go unrecognized till complications develop. We present three cases of interstitial ectopic pregnancies presenting in our hospital in a span of 1 year. Only one of them had pain in the abdomen at the time of presentation. All cases presented at around five to six weeks of gestation. Ultrasonography confirmed the diagnosis. One case was managed medically while in other two cases, there was a need of surgical management. There were no complications in all the cases. Thus, early presentation of cornual ectopic pregnancy results in satisfactory outcome. Hence, all pregnant women should undergo regular antenatal checkups with early scans once the urine pregnancy test come positive to confirm whether it is an intra uterine pregnancy or not.